Hyponatremia as Predictor of Adverse Outcome in Children with acute Lower Respiratory Tract Infections - Qahtan Alwan, Athraa; Metti Hanoudi, Basil; M. Mujbel , Abdallah (Hammurabi Journal of Medical Sciences, 2025)
Background: Lower respiratory tract infection is one of the major causes of mortality in children with estimated one million deaths every year. Hyponatremia is the most common electrolyte abnormality seen in lower respiratory tract infection. Objectives: To assess the impact of hyponatremia on morbidity and the course of illness in patients with acute lower respiratory tract infection. Materials and Methods: This prospective analytic study was conducted at the Child's Central Teaching Hospital from 1st December 2021 to 1st of October 2022. The study sample included 120 patients between 1- 168 month. Data on demographics, clinical status, biochemical status, and radiological findings were collected on admission. Follow-up serum sodium was carried out at 24 hours and 48 hours after admission. Result: The median age was 12 months old. The males were 51%. 5% of patients required respiratory care unit admission and endotracheal tube intubation; however, all patients were fully recovered. Concerning chest X- ray findings, the diagnosis of pneumonia was found in 67%; bronchiolitis in 27%; Empyema in 7% of cases. Hyponatremia in general and severe hyponatremia in particular were associated with higher duration of dyspnea (P-value <0.001), higher duration of oxygen requirement (P-value <0.001), longer time to effervescence (P-value = 0.02). Conclusion: In this study revealed that hyponatremia in general and severe hyponatremia in particular could adversely affect the morbidity in children with acute lower respiratory tract infection in terms of duration of hospitalization, duration of dyspnea, duration till effervescence, and duration of oxygen requirement.